2009
DOI: 10.1152/jn.00844.2009
|View full text |Cite
|
Sign up to set email alerts
|

Motor Outputs in a Multitasking Network: Relative Contributions of Inputs and Experience-Dependent Network States

Abstract: Network outputs elicited by a specific stimulus may differ radically depending on the momentary network state. One class of networks states-experience-dependent states-is known to operate in numerous networks, yet the fundamental question concerning the relative role that inputs and states play in determining the network outputs remains to be investigated in a behaviorally relevant manner. Because previous work indicated that in the isolated nervous system the motor outputs of the Aplysia feeding network are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 80 publications
2
54
0
Order By: Relevance
“…First, the auditory-motor link could represent a remnant of a phylogenic ready-for action system and be dedicated to low-level motor representations. Repetition priming of motoneuronal activity has been previously described in the feeding network of aplysia, where repeated stimulation led to an increase in the firing rate of neurons (Friedman et al 2009). The repetition enhancement has been interpreted as an intrinsic characteristic of a network dedicated to motor behavior (Friedman and Weiss 2010).…”
Section: Discussionmentioning
confidence: 82%
“…First, the auditory-motor link could represent a remnant of a phylogenic ready-for action system and be dedicated to low-level motor representations. Repetition priming of motoneuronal activity has been previously described in the feeding network of aplysia, where repeated stimulation led to an increase in the firing rate of neurons (Friedman et al 2009). The repetition enhancement has been interpreted as an intrinsic characteristic of a network dedicated to motor behavior (Friedman and Weiss 2010).…”
Section: Discussionmentioning
confidence: 82%
“…However, recent studies showed that for several minutes following EN stimulation, CBI-2 stimulation elicits egestive programs rather than ingestive programs (Friedman et al 2009;Proekt et al 2004Proekt et al , 2007Proekt et al , 2008. Thus EN stimulation induces a persistent egestive state that endows the network with slow dynamics to temporarily override the switch in the input.…”
Section: Introductionmentioning
confidence: 99%
“…2B). Changes in motor neuron activity are sufficient to alter the magnitude of radula opening movements [17]. …”
Section: The Aplysia Feeding Systemmentioning
confidence: 99%